Descentralização da Gestão Ambiental Pública: o licenciamento ambiental municipalizado em Araraquara-SP - Araujo, Clemerson Luiz Pereira de (2019)
The current essay aims to contribute to the discussions about the decentralization of public environmental management, in particular the municipalization of environmental licensing, going through the mechanisms used in the State of São Paulo, among them “Programa Município Verde/Azul” (Green/Blue Town Programme”) and the regulations on the municipalization of licensing. It also compares the procedures of environmental licensing performed in the town of Araraquara-SP with the ones performed by CETESB in São Carlos-SP. For this purpose, a documentary and bibliographic survey were done along with a semi structured questionnaire, in order to analyze the public agents impressions of both municipal and State government activities, as well as the users sense of satisfaction. The results showed that despite the initial expectations that municipal management could make the process more effective, there was no time reduction in municipal license releases as there was no investments to update the processes of analysis. Unlike the State administration, that after having gone through a virtualization process of license application, had the licenses for low environmental impact projects automatically released through an internet portal. However, we notice a greater accuracy in the town of Araraquara concerning the analysis and mitigation of the environmental impacts caused by licensed projects, besides a better relationship between municipal public agents and the community, proving the benefits of decentralization.